2017
DOI: 10.1111/medu.13417
|View full text |Cite
|
Sign up to set email alerts
|

Translating medical school social missions to student experiences

Abstract: Whether a medical school's social mission is focused on equity of access to the medical profession or on its graduates serving particular community needs, the mission principles need to be translated into practice. This translation process involves a series of externalisation and internalisation steps, each of which determines how much and what aspects of the mission are translated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Further qualitative work is exploring changes in student values and desire for service over the medical education program at THEnet schools [ 29 ] and the role of faculty motivation and faculty background in contributing to these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Further qualitative work is exploring changes in student values and desire for service over the medical education program at THEnet schools [ 29 ] and the role of faculty motivation and faculty background in contributing to these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…18 Yet, studies have shown that medical students with a clear perception of social mission with opportunities to directly experience it during their education have a better understanding of not just the term, but they operationalise it within their own practice. 19,20 Social awareness and a proclivity towards social justice require the development of a socially responsible value and belief system. However, it is not sufficient for creating socially accountable medicine in the absence of institutional responsibility.…”
Section: Discussionmentioning
confidence: 99%
“…They need to plan, implement and assess their service, research and training in cooperation and collaboration with the civil society leaders, lawmakers, service providers and non-governmental organizations. Medical schools need to advocate for health promotion, take on leadership in social responsibility projects/studies enhancing stakeholder participation and create awareness in the society with relevant information and outcomes (Ellaway 2018). The recommendations in this theme is covered under the heading 'creating responsive and responsible governance of the medical school' in the Global Consensus document (https://healthsocialaccountability.org).…”
Section: E24mentioning
confidence: 99%